PENGARUH KONFLIK PERAN, JOB INSECURITY, KEPUASAN KERJA DAN KOMITMEN ORGANISASIONAL TERHADAP KEINGINAN BERPINDAH STAF PADA KANTOR AKUNTAN PUBLIK - Purnawati, Fitria (Jurnal Analisis Bisnis Ekonomi, 2007)
The study investigates the turnover intension in public accountant in Jogjakarta. The data were collected by survey questioner. This, the paper examines positive effects of role conflict, and job insecurity, and negative effects job satisfaction, and organizational commitment on turnover intension. A Multiple Regression was used to test hypothesized linked. Support was found for the positive effects of role conflict, and jon insecurity, and negative effects job satisfaction, and organizational commitment on turnover intension public accountant.